Peran Ganda Komunitas Perempuan Pencungkil Kelapa Dalam Tinjauan Hukum Islam di Kelurahan Mendahara Ilir, Kecamatan Mendahara, Kabupaten Tanjung Jabung Timur - Wandi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the dual roles of women in the coconut husking community in Mendahara Ilir, as well as to review these roles from the perspective of Islamic law. The dual roles referred to include domestic roles as wives and housewives, and public roles as income earners in the informal sector. This research employed a qualitative approach with a field study method through observation, interviews, and documentation. The findings indicate that women in this community make significant contributions to the family economy while continuing to fulfill their household responsibilities. From the perspective of Islamic law, these dual roles are permissible as long as they do not neglect primary family obligations and do not conflict with sharia principles. Islamic law appreciates women’s hard work and recognizes their right to work, provided that they maintain proper conduct, family responsibilities, and Islamic values. Therefore, the dual roles of women coconut huskers in this area can be categorized as a form of social ijtihad that aligns with the objectives of maqashid sharia, particularly in the aspects of protecting life and property